Application of Stokes' Law and Capillary Tube Method in Measuring Fluid Viscosity - -, taruna - (Asian Journal of Science Education, 2025)
Viscosity is an important characteristic of fluids that plays a significant role in various applications in mechanical engineering, chemistry, and industry. This research focuses on examining the use of Stokes' Law and the capillary tube method in determining fluid viscosity through an experimental approach. In the Stokes' Law approach, measurements are made by observing the falling velocity of a solid ball in the fluid, while in the capillary tube method, calculations are made based on the fluid flow rate through the capillary tube by considering the pressure difference and the tube length. The experimental results show that both techniques can be used to determine viscosity values, although with varying accuracy. The Stokes' Law method is more practical to apply, but the results are affected by fluid homogeneity and the size of the test ball. Meanwhile, the capillary tube method produces more consistent data in fluids with low to medium viscosity. Comparison of the results shows differences in values, but they are still within the experimental tolerance range. Therefore, the application of these two methods can be used as an alternative practicum activity to deepen the understanding of the basic concepts of fluid mechanics while providing direct experience in measuring the physical properties of fluids.